1995
DOI: 10.1016/0014-5793(95)00179-d
|View full text |Cite
|
Sign up to set email alerts
|

Primary sequence and post‐transcriptional modification pattern of an unusual mitochondrial tRNAMet from Tetrahymena pyriformis

Abstract: We have now isolated and characterized the smallest T. pyriformis mitochondrial tRNA and we show here that it has the primary sequence that we had predicted from the trnM sequence. The transcript also contains a Y-terminal CCA sequence, not encoded in the mtDNA, as well as several modified nucleosides characteristic of known functional tRNAs. Materials and methodsT. pyriformis, amicronucleate strain ST (obtained from Y. Suyama, Department of Biology, University of Pennsylvania), was grown at 28°C with constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In Oxytricha , we think it is unlikely that RNA editing removes all the stops necessary to join the nad2 ORFs (at least two stop codons would need to be eliminated or read through). Instead, it appears that, like nad1 (Seilhamer, Gutell, et al 1984; Seilhamer, Olsen, et al 1984; Heinonen et al 1987; Pritchard et al 1990; Schnare et al 1995; Burger et al 2000), this gene is not transspliced (supported by cDNA PCR results, data not shown), and therefore, the gene pieces are translated as separate subunits that require co-assembly to form the functional protein structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In Oxytricha , we think it is unlikely that RNA editing removes all the stops necessary to join the nad2 ORFs (at least two stop codons would need to be eliminated or read through). Instead, it appears that, like nad1 (Seilhamer, Gutell, et al 1984; Seilhamer, Olsen, et al 1984; Heinonen et al 1987; Pritchard et al 1990; Schnare et al 1995; Burger et al 2000), this gene is not transspliced (supported by cDNA PCR results, data not shown), and therefore, the gene pieces are translated as separate subunits that require co-assembly to form the functional protein structure.…”
Section: Resultsmentioning
confidence: 97%
“…Ciliate mitochondrial genomes are both gene-rich and relatively large (20–60 kb) (Gray et al 1998), though many mitochondrial genes remain unclassified (Pritchard et al 1990; Burger et al 2000; Brunk et al 2003; Moradian et al 2007), in part due to their extreme divergences from other eukaryotic mitochondrial genomes (Pritchard et al 1990; Burger et al 2000; Moradian et al 2007). Split ribosomal RNA and nad1 genes (Seilhamer, Gutell, et al 1984; Seilhamer, Olsen, et al 1984; Schnare et al 1986, 1995; Heinonen et al 1987; Pritchard et al 1990; Burger et al 2000) were also discovered in ciliate mitochondria. Some anaerobic ciliates contain hydrogen-producing organelles, or hydrogenosomes, that may derive from mitochondria, and the ciliate Nyctotherus ( Armophorea ) has a partially sequenced hydrogenosome genome (Akhmanova et al 1998; Boxma et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We previously obtained similar results when sequencing the D loops of tRNAs. 35,36 The sequencing results for LSU rRNA position 3540 are diagnostic of 3-methyluridine (m 3 U), 37 which gives a normal band in alkali ladders (Fig. 7e) but yields very intense bands in the U and C lanes of chemical sequencing gels (Fig.…”
Section: Detection Of Base Modifications As Anomalies In Sequencing Lmentioning
confidence: 97%
“…The sequence of the mature tRNA corresponding to the tRNA gene sequence DX3800, published recently (Schnare et al, 1995), is incorporated in the Table, but has not yet received its ID number in the tRNA Compilation.…”
Section: Shows the Number Of Base-pairs In The Tstem Column C Shows mentioning
confidence: 99%